Effect of imagery training on skeet shooting accuracy of high school students in the People`s Republic of China - Guo, W.; Rittisom, S.; Watchayakarn, K. (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Imagery training enhances mental visualization skills, helping high school students improve focus and consistency in skeet shooting. Athletes can refine their technique and boost accuracy without physical practice by mentally rehearsing the shooting process. This study investigated and compared the effects of imagery training on skeet shooting accuracy among high school students from Shenzhen Yuxin High School, Shenzhen City, Guangdong Province, China.